Czym są marksistowskie badania szkolnictwa wyższego? - Szadkowski, Krystian; Krzeski, Jakub (Praktyka Teoretyczna, 2015)
In this short introduction to the thematic issue of Theoretical Practice we draw on the Marxist concept of critique to explain how Marxist higher education research could be understood as a constituting practice within-against-beyond the contemporary university in crisis.